Monitoring and Detection of Hotspots using Satellite Images - Mohamad Yusof, Juliana (Universiti Teknologi Petronas, 2006)
Nowadays, the usage of optical remote sensing NOAA-AVHRR satellite data is getting familiar as it is known can save cost in order to capture a wide coverage of ground image. The captured images are meaningful after several processes done over it to produce hotspot detection. Developing a specific database to store information of Hotspots (LAC images) would make datamanagement and archiving purpose in more efficient and systematic way. Real-time data gathered are monitored countries such as Malaysia, Thailand, Singapore, Indonesia and Brunei within the region of NOAA Satellite coverage area. PostGIS, PostgreSQL, Mapserver and Autodesk MapGuide Studio software are to be studied as a guide to develop a system with simple database using object-relational database management system to store raster and vector images. This paper describes a solution for efficient handling of large raster image data sets in a standard object-relational database management system. By means of adequate indexing, retrieval techniques and multi resolution cell indexing (Quad-Tree) can be achieved using a standard DBMS, even for very large satellite images. Single image will be divided equally into 64 small squares (3 levels of image hierarchy - each level has 4 sub images of the higher image). Partial information of Daily Haze report (processed Hotspot on image map) produces by NREB can be viewed using web-based application. The final product of this project is a web-based application for displaying Hotspots on maps (combination of raster and vector images) with the ability to search record from database and functions to zoom in or zoom out the map. The objective of this paper is also to show the way satellite images and descriptive information are combined and amalgamated to form an Internet or Intranet application.